How Managers' Green Transformational Leadership Affects a Firm's Environmental Strategy, Green Innovation, and Performance: The Moderating Impact of Differentiation Strategy - Ozgul, Burcu; Zehir, Cemal (MDPI, 2023)
No prior literature has investigated the effect of managers' green transformational leadership (GTL) on financial performance (FP). The current study introduces an original research framework with the aim of filling in this gap. This study introduces a completer analytical framework by considering the direct impacts of managers' GTL on FP and the indirect impacts of managers' GTL under the joint action of corporate environmental strategy (CES), green product innovation (GPT), and green process innovation (GPI). Furthermore, based on the question of how enterprises can earn profit from GPT, analyzing the moderator impact of differentiation strategy on the relationship between GPT and FP is also within the context of the present study. The data collected from 315 firms with the ISO 14001 certificate in the First and Second 500 Industrial Enterprises List of Turkey in 2018 were tested in the SmartPLS 3 analysis program. The empirical evidence shows that managers' GTL affects FP both directly and indirectly through CES and GPI. However, it is concluded that GPT does not have a direct positive impact on FP. Considering GPT and differentiation strategy jointly, it is observed that its relationship with FP is positive and significant.
Keywords: green transformational leadership; corporate environmental strategy; green innovation; differentiation strategy; financial performance; RESOURCE-BASED VIEW; ECO-INNOVATION; PRODUCT INNOVATION; SUPPLY CHAIN; SUSTAINABILITY STRATEGY; EMPIRICAL-EVIDENCE; CORPORATE; RESPONSIBILITY; MARKET; Science & Technology - Other Topics; Environmental Sciences & Ecology